Human intestinal epithelial cells promote the differentiation of tolerogenic dendritic cells. Issue 11 (30th June 2009) - Iliev, I D; Spadoni, I; Mileti, E; Matteoli, G; Sonzogni, A; Sampietro, G M; Foschi, D; Caprioli, F; Viale, G; Rescigno, M
Abstract : Objective: In mice, a subpopulation of gut dendritic cells (DCs) expressing CD103 drives the development of regulatory T (Treg ) cells. Further, it was recently described that the cross-talk between human intestinal epithelial cells (IECs) and DCs helps in maintaining gut immune homeostasis via the induction of non-inflammatory DCs. In this study, an analysis was carried out to determine whether IECs could promote the differentiation of CD103 + tolerogenic DCs, and the function of primary CD103 + DCs isolated from human mesenteric lymph nodes (MLNs) was evaluated. Methods: Monocyte-derived DCs (MoDCs) and circulating CD1c + DCs were conditioned or not with supernatants from Caco-2 cells or IECs isolated from healthy donors or donors with Crohn's disease and analysed for their ability to induce Treg cell differentiation. In some cases, transforming growth factor β (TGFβ), retinoic acid (RA) or thymic stromal lymphopoietin (TSLP) were neutralised before conditioning. CD103 + and CD103 − DCs were sorted by fluorescence-activated cell sorting (FACS) from MLNs and used in Treg cell differentiation experiments. Results: It was found that human IECs promoted the differentiation of tolerogenic DCs able to drive the development of adaptive Foxp3 + Treg cells. This control was lost in patients with Crohn's disease and paralleled a reduced expression of tolerogenic factors by primary IECs. MoDCs differentiated with RA or IEC supernatant upregulated the expression of CD103. Consistently, human primary CD103 + DCs isolated from MLNs were endowed with the ability to drive Treg cell differentiation. This subset of DCs expressed CCR7 and probably represents a lamina propria-derived migratory population. Conclusions: A population of tolerogenic CD103 + DCs was identified in the human gut that probably differentiate in response to IEC-derived factors and drive Treg cell development.